Contribution to the knowledge on the Oriental genus Perittopus Fieber, 1861 (Hemiptera: Heteroptera: Veliidae) with descriptions of four new species from China and Thailand - Ye, Zhen; Chen, Pingping; Bu, Wenjun (Zootaxa, 2013)
Five species of the genus Perittopus Fieber, 1861 from China and Thailand are treated in this paper including four new species: P. crinalis sp. nov., P. falciformis sp. nov., and P. yunnanensis sp. nov. are from Yunnan Province, China; and P. zhengi sp. nov. from Chiang Mai, Thailand. The morphological descriptions are given for all the treated species. The photographs and the drawings of female habitus and male and female diagnostics are provided. A key to these five species is provided. The discussion on the identity of P. asiaticus Zettel, 2001 is given.